2021
DOI: 10.1016/j.chroma.2020.461721
|View full text |Cite
|
Sign up to set email alerts
|

A unique data analysis framework and open source benchmark data set for the analysis of comprehensive two-dimensional gas chromatography software

Abstract: Comprehensive two-dimensional gas chromatography (GC × GC) is amongst the most powerful separation technologies currently existing. Since its advent in early 1990, it has become an established method which is readily available. However, one of its most challenging aspects, especially in hyphenation with mass spectrometry is the high amount of chemical information it provides for each measurement. The GC × GC community agrees that there, the highest demand for action is found. In response, the number of softwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 29 publications
(21 reference statements)
0
16
0
Order By: Relevance
“…Typically, cryogenically modulated peaks present peak widths ranging between 0.1 and 0.2 s. In this regard, the modeling errors could be estimated to 2–3 peak widths. Additionally, the comparison of multiple commercially available GC × GC software highlighted the presence of an average difference of 0.15 s between the reported 2 t r when changing software due to differences in the data transformation algorithms . In light of this comparison, the errors yielded by the present approach do not seem outrageous but rather lie in quite a reasonable range.…”
Section: Resultsmentioning
confidence: 68%
“…Typically, cryogenically modulated peaks present peak widths ranging between 0.1 and 0.2 s. In this regard, the modeling errors could be estimated to 2–3 peak widths. Additionally, the comparison of multiple commercially available GC × GC software highlighted the presence of an average difference of 0.15 s between the reported 2 t r when changing software due to differences in the data transformation algorithms . In light of this comparison, the errors yielded by the present approach do not seem outrageous but rather lie in quite a reasonable range.…”
Section: Resultsmentioning
confidence: 68%
“…Recently, more open-source data sets have become available; for instance, Focant and co-workers have provided two data sets, consisting of either five fruit beers 32 or nine flavored chocolate samples, 143 that can be used to benchmark the performance of nontargeted methods. Using the chocolate data set, Weggler et al demonstrated that both the number of peaks aligned in the final peak tables and clustering on the PCA scores plot differed among eight commercial software packages for GC×GC data analysis.…”
Section: ■ Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Using the chocolate data set, Weggler et al demonstrated that both the number of peaks aligned in the final peak tables and clustering on the PCA scores plot differed among eight commercial software packages for GC×GC data analysis. 143 Because it is difficult to ascertain the differences in proprietary vendor software, there has been increased interest in developing free and open-source software (FOSS). 144−147 With FOSS, the user can see exactly how the software treats their data and make changes to the software if necessary.…”
Section: ■ Conclusion and Future Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations